2019
DOI: 10.1186/s40478-019-0853-9
|View full text |Cite
|
Sign up to set email alerts
|

A metastable subproteome underlies inclusion formation in muscle proteinopathies

Abstract: Protein aggregation is a pathological feature of neurodegenerative disorders. We previously demonstrated that protein inclusions in the brain are composed of supersaturated proteins, which are abundant and aggregation-prone, and form a metastable subproteome. It is not yet clear, however, whether this phenomenon is also associated with non-neuronal protein conformational disorders. To respond to this question, we analyzed proteomic datasets from biopsies of patients with genetic and acquired protein aggregate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 41 publications
(78 reference statements)
0
11
0
Order By: Relevance
“…This observation led to the “living on the edge” hypothesis that suggests that protein abundance is tightly regulated to an optimal level, sufficient for proteins to develop their biological function but low enough to maintain their solubility [84] . Proteins exceeding their critical concentration are considered supersaturated and constitute a metastable subproteome, often associated with diseases [85] , [86] , [87] , [88] .…”
Section: Resultsmentioning
confidence: 99%
“…This observation led to the “living on the edge” hypothesis that suggests that protein abundance is tightly regulated to an optimal level, sufficient for proteins to develop their biological function but low enough to maintain their solubility [84] . Proteins exceeding their critical concentration are considered supersaturated and constitute a metastable subproteome, often associated with diseases [85] , [86] , [87] , [88] .…”
Section: Resultsmentioning
confidence: 99%
“…A breakdown of the protein content of ALS‐related inclusion bodies indicated that co‐aggregating proteins are either interaction partners of the major protein constituents (TDP43, SOD1, FUS), or display supersaturated expression levels and increased metastability towards aggregation, suggesting that progressive impairment of the proteostatic mechanisms can trigger their co‐deposition in motor neurons [102]. Recently, it was shown that protein supersaturation levels are not only linked to neurodegenerative disorders, as a similar metastable subproteomic population was shown to dictate the formation of inclusions in muscular proteinopathies [103].…”
Section: Deciphering the Role Of Brain Heterogeneity In Aggregation D...mentioning
confidence: 99%
“…Protein supersaturation refers to proteins that are expressed at high levels relative to their intrinsic propensity to aggregate, which makes them vulnerable to aggregation. Supersaturation has been shown to underlie the widespread protein aggregation observed in age-related neurodegenerative diseases, and in general aging ( Ciryam et al, 2015 ; Ciryam et al, 2019 ; Freer et al, 2019 ; Kundra et al, 2017 ; Noji et al, 2021 ). The relevance of supersaturation is underlined by the notion that evolutionary pressures appear to have shaped proteomes along its lines, so that at a global level protein abundance is inversely correlated with aggregation propensity ( Tartaglia et al, 2007 ).…”
Section: Resultsmentioning
confidence: 99%